Analisis Faktor-Faktor Yang Mempengaruhi Tingkat Keberdayaan Remaja Tentang Kesehatan Reproduksi Di SMA Negeri 1 Kepanjen - Dessy Abrillia Sahari; Rita Yulifah; Dwi Yuliawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Adolescence is a phase of life between childhood and adulthood, aged 10-19 years, where the important period for reproductive life, because adolescents begin to experience hormonal, physical, psychological and social changes. Adolescents as the next generation of the nation are vulnerable to deviant reproductive health behavior, which will have impacts such as sexually transmitted diseases, unwanted pregnancies, early marriage, abortion and dropping out of school. The purpose of this study was to analyze the factors that influence the level of adolescent empowerment regarding reproductive health. The type of research used is descriptive analytical with a cross-sectional approach. The population in this study were female adolescents in grade XI at SMA Negeri 1 Kepanjen, the number of samples was 75 respondents taken using the proportional random sampling technique. Data collection methods by filling out questionnaires. Univariate data analysis with frequency distribution and bivariate using the chi square test. 95% confidence interval with a significance limit of p <0.05. The results showed a p value of 0.000 <0.05, meaning that there is a significant relationship between the role of teachers, the role of parents and the role of peers on the level of adolescent empowerment regarding reproductive health. Researchers concluded that the more sources of information that adolescents obtain from various sources and the more frequently adolescents implement reproductive health behaviors, the more adolescents will be able to empower themselves.